Antibacterial Activity of Natural Mouthwash Against Bacteria Isolated from the Oral Cavity: Aktivitas Antibakteri Obat Kumur Alami Terhadap Bakteri yang Diisolasi dari Rongga Mulut - Mohammad M. Salih; Saja A. Abdulkareem; Nabaa A. Khalil (Academia Open, 2026)
General Background: Oral hygiene is essential for preventing oral diseases, and interest in herbal formulations has increased due to concerns regarding side effects of chemical mouthwashes. Specific Background: Plant-derived ingredients such as pomegranate peel, clove, peppermint oil, rose water, and rock salt contain antimicrobial compounds that may support oral health. Knowledge Gap: However, limited studies have evaluated combined natural formulations against bacteria isolated from the oral cavity. Aims: This study aimed to examine the antibacterial activity of a natural mouthwash formulation against oral bacteria and compare it with a synthetic mouthwash. Results: Six concentrations of the formulation were tested against Klebsiella pneumoniae, Proteus mirabilis, and Enterococcus faecalis. The results showed that K. pneumoniae and P. mirabilis were sensitive to all concentrations, with inhibition zones reaching 26 mm and 28 mm respectively, while E. faecalis showed resistance to several concentrations. Novelty: The study presents a combined formulation of pomegranate peel and clove extracts as a natural mouthwash with antibacterial activity against multiple oral bacteria. Implications: These findings indicate that herbal mouthwash formulations may provide a natural alternative for oral hygiene applications. Highlights: • Certain natural formulations produced bacterial inhibition zones up to 28 mm• Gram-negative isolates showed broader susceptibility than Enterococcus faecalis• Combined plant extracts and mineral components demonstrated measurable antimicrobial activity Keywords: Natural Mouthwash; Antibacterial Activity; Oral Cavity Bacteria; Pomegranate Peel Extract; Clove Extract